Microfacies Analysis and Stratigraphic Development of the Mishrif Formation in the Eastern of the Mesopotamian Zone, Southeastern Iraq - Nasser, Medhat E. (Iraqi Journal of Science, 2018)
Mishrif Formation is the most important succession in the southern part of Iraq and has extensive distribution in the Arabian Plate. The present study focuses upon the sequence stratigraphy and development of Mishrif Formation basin in four oil fields within the eastern part of the Mesopotamian Zone are:- Halfaya (Hf-1), Noor (No-1) and Abu Ghirab (AG-3) and Fauqi oil fields (Fq-1). There are several types of microfacies were distinguished in the succession of the Mishrif Formation. Their characteristic of the grain types and carbonate texture enabled to interpret of five facies associations (depositional environments) were observed in this formation, they are: deep marine, shallow open marine, Shoal, rudist biostorm, and shallow restricted associations facies. The stratigraphic development of Mishrif succession in the studied oil fields was summarized by three depositional stages during the Cenomanian-Early Turonian cycle:- First stage:- the basin of Rumaila Formation during this stage was continued to deposition the lower part of Mishrif Formation within the deep marine environment. The end of deposition in this basin (Rumaila basin) was represented by shallow open marine associated facies in the studied area. The High stand sequence distinguished by deposition the deep marine facies and the shallow open marine as two cycle in the southwest, while to the northeast one cycle. The end of the first stage was finished by the shoal facies in all studied area to mark a sequence boundary type II (prograde stage A). Second stage:- the basin was developed from shoal to biostorm facies association with slow sea level rise. The deposition of the open marine associated facies within the biostorm-shoal sequence marked the mfs surface. The final step of this stage was shown the shallowing up-ward by overlaying the shallow open marine association facies upon the biostorm and shoal. At the end of this period, the lagoon/restricted facies were spread in the studied area to mark the prograde stage B as sequence boundary type II. Third stage:- the sea level raised in the southwest direction as open sea association facies, while to the northeast the restricted facies was dominated. This sequence appeared the shoal facies underly the open sea facies marked the mfs surface to start the final high stand deposition overly the restricted facies. This stage is representing the prograde stage C for the Mishrif Formation, where ended the deposition to mark the unconformable surface (SBI) with Khasib Formation.